Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dinas Koperasi UKM Karawang - Saputra, Bagas; Suroso, Suroso; Anggela, Flora Patricia (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The aim of this research is to determine the influence of work discipline and work environment on the performance of employees of the Karawang UKM Cooperative Service. This research is verification research with a quantitative approach. The population of this study was employees of the Karawang UKM Cooperative Service, totaling 45 respondents. Sampling used a total sampling technique with a total of 45 respondents. The data collection method is using a questionnaire and analysis tools using SPSS 22 with a multiple linear regression approach. The results of the research show that there is a partial influence between the Work Discipline variable (x1) on Employee Performance (y) with a calculated t value > t table (5.502 > 2.014) and there is a partial influence between the Work Environment variable (x2) on Employee Performance (y) with calculated t value > t table (2.280 > 2.014) andsimultaneously there is an influence of Work Discipline Variables (x1) and Work Environment (x2) on employee performance (y) withcalculated F value > F table (27.876 > 3.22).